Avaliação das condições posturais dos trabalhadores na produção de carvão vegetal em cilindros metálicos verticais - Maia, Ivana Márcia Oliveira (2008)
Considering the posture importance to the health of workers in the production process of charcoal, this ergonomic research based on a biomechanical focus aims on the evaluation of the posture adopted by these workers on the production of charcoal in vertical metal cylinders. Thus, it was verified the incidence of pain and/or musculoskeletal injuries to the workers in charcoal production. Also, it was evaluated the weight carried by the worker performing their daily tasks and the positions taken by workers during these tasks execution. The research is qualitative and applied, and their goals are descriptive, what is associated to the inductive method. Applying the Ergonomic Analysis of Labor, the data collection was done from workers direct observation, registration of images, interviews, application of a Diagram proposed by Corlett and Manenica and analysis of data made with a system posture analysis based on the OWAS method: the software WinOwas specific for ergonomic research. The main results of the research show that there postures with risks in the four levels of musculoskeletal injuries classified by OWAS, concluding that the method is imperative for ergonomic recommendations for minimizing or eradication of suffering injury and worker’s postural constraints.